Divide each term in <math><mstyle displaystyle="true"><mi>s</mi><mi>l</mi><mi>o</mi><mi>p</mi><mi>e</mi><mo>=</mo><mo>-</mo><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mi>l</mi><mi>o</mi><mi>p</mi><mi>e</mi></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>l</mi></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>o</mi></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>p</mi></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>e</mi></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>s</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Move the negative in front of the fraction.

Use the formula for the equation of a line to find <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

Substitute the value of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> into the equation.

Substitute the value of <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> into the equation.

Substitute the value of <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> into the equation.

Find the value of <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

Rewrite the equation as <math><mstyle displaystyle="true"><mo>-</mo><mfrac><mrow><mn>3</mn></mrow><mrow><mi>l</mi><mi>o</mi><mi>p</mi><mi>e</mi></mrow></mfrac><mo>⋅</mo><mn>2</mn><mo>+</mo><mi>b</mi><mo>=</mo><mo>-</mo><mn>4</mn></mstyle></math> .

Simplify each term.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mfrac><mrow><mn>3</mn></mrow><mrow><mi>l</mi><mi>o</mi><mi>p</mi><mi>e</mi></mrow></mfrac><mo>⋅</mo><mn>2</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn></mrow><mrow><mi>l</mi><mi>o</mi><mi>p</mi><mi>e</mi></mrow></mfrac></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Move the negative in front of the fraction.

Add <math><mstyle displaystyle="true"><mfrac><mrow><mn>6</mn></mrow><mrow><mi>l</mi><mi>o</mi><mi>p</mi><mi>e</mi></mrow></mfrac></mstyle></math> to both sides of the equation.

Now that the values of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> (slope) and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> (y-intercept) are known, substitute them into <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> to find the equation of the line.

Do you know how to Write in Slope-Intercept Form (2,-4) , slope=-3? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.